From Crisis to Crisis - Ana Podvršič; Lukas Schmidt (Revue de la Régulation)
The article explores the elements that led Slovenia to face another major crisis within the Eurozone turmoil less than twenty years after its political separation from Yugoslavia. The analysis builds on a combined theoretical framework of the insights from dependency school and regulation theory. The outbreak of the 1980s Yugoslav crisis and the IMF’s involvement into the domestic policy-making revealed that Slovenian post-war industrialization was dependent on imports and foreign credits. The Washington Consensus structural adjustments eased a shift in the post-war development pattern and deepened dependent integration in the European structures. During the 1990s, a labour-inclusive accumulation regime stabilized the pattern of export-led industrialization, a smaller reliance on FDI and a state-managerial control of domestic production. After 2000, however, the availability of cheap credits on the European markets, an accelerated transfer of state polices on the European level and the weakening of labour bargaining power created conditions for a dependent financialization of the Slovenian economy.